Effect of Glass Powder on Some Mechanical Properties of Polymer Matrix Composite Material - Musa, Bushra H (Al-Nahrain Journal of Science, 2018)
This research deals with the study of the effect of adding glass powder of grain size (35μm) with different volume fraction (10%, 20%) to the blend of unsaturated polyester and polyurethane using hand lay-up method, after preparing the matrix from weight fraction (90%) of Unsaturated polyester and (10%) of polyurethane. The results have shown that the addition of particles to the polymer blends lead a great extent in mechanical properties, since testing bending, Shore D hardness and impact strength. It has shown that the values of young modulus, impact strength and hardness were increased with increasing of volume fraction of glass powder. Fracture surface of the samples were examined by using optical microscope with magnification (40 X) and the results showed that the nature of fracture is seems brittle fracture for all samples.